Wiedza i świadomość polskich, czeskich i słowackich studentów na temat zmian hormonalnych w cyklu życia człowieka - Leżucha, Magdalena; Czerwiec, Karolina; Nodzyńska-Moroń, Małgorzata; Pasternáková, Lenka; Studnicki, Emanuel; Sirotek, Vladimir (Kultura-Społeczeństwo-Edukacja, 2025)
There are many environmental factors that can affect a person’s fertility and rate of development during adolescence. The use of psychoactive substances during puberty, a time when testosterone and oestradiol levels begin to exceed childhood levels, increases the likelihood of psychiatric disorders in adulthood; in turn, at menopause, oestrogen deficiency can cause psychological, physical and endocrine changes, including sexual dysfunction. The study aimed to diagnose students’ knowledge of hormonal changes in the human life cycle. The study was conducted at three universities – in Poland, the Czech Republic and Slovakia. A total of 450 stu-dents participated in the study (172 from Poland, 99 from the Czech Republic and 179 from Slovakia). The research sample was selected based on the assumption that there are differences in awareness of sexual development in Polish, Czech and Slovak society. The research was conducted by means of a diagnostic survey with a questionnaire technique.The analysis of the survey results showed that students’ knowledge of hormonal changes in the human life cycle is insufficient. It was shown that there is a need to pay attention to deepen and consoli-date the knowledge of students, especially students of education/teaching, regarding problems related to biological, social and environmental factors affecting hormonal changes in the human life cycle; with satisfactory knowledge of the consequences of psychoactive substance use or environmental factors that may affect the menstrual cycle.